배양미생물과 가축분뇨발효액비의 시비가 골프코스 토양 중 대취분해에 미치는 영향 - 함선규(Suon Kyu Ham); 임지연(Ji Yeon Lim); 이영민(Yeong Min Lee) (Weed & turfgrass science, 2014)
The purpose of this experiment is for investigating how much the amino acid liquid fertilizer and composted liquid manure, culture microorganism effect on the breeding of grasses and knowing the extent of the thatch content through an analysis of the soil. For testing about soil chemical, the quality of grasses, and the extent of the thatch content in the soil, we cultivated 6 kinds of microorganisms having the effect of thatch dissolution and sprayed these 6 microorganisms with composted liquid manure and the amino acid liquid fertilizer on the place Creeping bentgrass have planted. This conduction started from June to October, 2012 and 2013 (The interval: 2 weeks). In the result of the turf growth, there is no big difference between soil chemical and trace element. And we can know Leaf Color Index, Chlorophyll Index and Root Length are almost same as among treatment. In conclusion, the mixing fertilization of culture microorganism and composted liquid manure is better effective than the traditional fertilization. And it can be expected the effect of the quality of grass and Thatch decomposition in soil. 본 연구에서는 골프장 잔디재배 토양에 축적되어 과습을 유발하여 잔디뿌리의 호흡작용을 방해하고 각종 병의 서식처가 되는 토양대취의 분해여부를 조사하기 위해 2012년부터 2년간 토양온도가 높은 기간인 6월부터 10월까지 인천시 중구 소재 스카이72 골프크럽 하늘코스 2홀 페어웨이에서 배양미생물과 가축분뇨액비를 혼용 처리하여 토양화학성, 잔디품질 및 토양 중의 대취분해여부에 대해 조사하였다. 공시 배양미생물은 연구소자체 선발하여 예비실험에서 대취분해 효과가 있었던 6종의 혼합미생물을 1톤 규모로 대량 배양하여 시험에 사용하였으며, 배양미생물에는 가축분뇨액비와 배양미생물의 토양 중 먹이역할을 하는 탄소화합물함유 아미노산액을 혼용하여 처리하였다. 시험결과, 처리구별 토양의 화학성과 미량원소 함유량은 큰 차이는 보이지 않았으나 엽색지수와 엽록소지수 및 잔디뿌리길이는 거의 동일하게 나타났다. 또한 토양 중 대취함량은 무처리보다 배양미생물과 가축분뇨액비를 혼용한 처리구에서 대취분해정도가 더 높게 나타났다. 따라서 한지형잔디로 식재된 골프코스 페어웨이 관리 시에 잔디품질 유지와 토양 중 대취분해를 위해서는 배양미생물과 가축분뇨액비의 혼합한 시비가 관행적인 화학비료시비보다 더 유리하다고 사료된다.